Using the VERA-2R, professional and organisational aspects - Duits, Nils; Overdulve, Carina; Kempes, Maaike (Frontiers in Psychiatry, 2023)
Introduction Violent extremism risk assessments of individuals suspected or convicted of terrorism are relevant for legal decisions, in prison and probation settings, and in inter-professional risk collaboration. These risk assessment reports by professionals should be applicable to and usable for the different judicial contexts. Informal and formal clinical practice evaluations, in the form of practitioners feedback and standardised evaluation of professional violent extremism risk reports are needed to gain insight in the use and quality of violent extremism risk assessments. Methods In this study we examined how forensic professionals from three different countries (Sweden, Belgium and the Netherlands) use the VERA-2R in different judicial contexts. We also investigated which organizational aspects are important for the use of the VERA-2R. We focused on the perspective of the forensic professionals and their judicial organisations. We did a standardised survey among 86 VERA-2R trained professionals and a standardised interview with 20 executives and managers of organizations working with the VERA-2R. Results This study showed that professionals find the VERA-2R useful for structuring information and speaking a common risk language. However, using the VERA-2R comes with a variety of challenges, both on the professional and organisational level. VERA-2R trained professionals had few opportunities to use the instrument and when they did, they were not always offered regular supervision, intervision and booster training. Also, organisational issues in collaboration between judicial partner organisations and the lack of risk transfer information to professionals came to light. Discussion More research on the topic of risk transfer is needed. Policy implications are advised, for example the development of booster trainings, more organizational support, regulations on re-assessments, providing expertise and knowledge to indirect stakeholders and clear writing guidelines.